ANTICANCER EFFECT OF AFRICAN LEAVES (VERNONIA AMYGDALINA DEL.) TO T47D CELL RESISTANT - Lifiani, Rialita; Harahap, Urip; Hasibuan, Poppy Anjelisa Zaitun; Satria, Denny (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: African leaves (Vernonia amygdalina Del) have medical effect to threat many kind of diseases, and recently, it is suggested have anticancer effect. Therefore, this study is held to testing anticancer activity of extract African leaves to T47D cell resistant. Method: Cytotoxic activity was determined in vitro used 3-(4,5-dimethylthiazole-2-yl)-2,5-diphenyl tetrazolium bromide method. Analysis of cell cycle and apoptosis were determined with flow cytometry method. Results: Examination cytotoxicity of extract n-hexana African leaves (ENDA), extract ethyl acetate African leaves (EEADA), and extract ethanol African leaves (EEDA) to T47D cell were showed with IC50 values 164.85Â±1.88 Î¼g/mL for ENDA; 55.50Â±0.79 Î¼g/mL for EEADA and 311.72Â±4.15 Î¼g/mL for EEDA. Therefore, EEADA has the most active activity as anticancer. Moleculer evolution assay produced T47D cell resistant. Examination toxicity of EEADA to T47D-cell resistant showed IC50 values 59.19Â±0.55 Î¼g/mL. EEADA might able inhibit cell cycle at G0-G1 phase and increased apoptosis of T47D cell resistant. Conclusion: This study shows that EEDA can be developed as cochemotheraphy to breast cancer with inhibits cel cycle and increase apoptosis.